Optimum control with minimum battery storage for islanded microgrid operation powered by solar PV - Ravindran, N.; Kokulavasan, T.; Nithusiga, S.; Ahilan, K.; Atputharajah, A. (2023 Innovations in Power and Advanced Computing Technologies (i-PACT), 2023)
The application of islanded micro grid, powered by renewable energy sources such as solar PV is getting more vital due to the environmental crises of fossil fuel. Further to the greenhouse gas emission, the present economic crises pushes the utilities to look for alternative solutions to supply increasing customer demands. This challenge can be mitigated by using freely available solar power with the support of batteries. Presently batteries are expensive therefore an optimized solution is required. This paper proposed an optimized solution, which will be benefitted by the utility as well as the customer, based on their purchasing power. This scenario is analyzed with optimum control mechanism based on state of energy (SOE) of the battery. Hence the selection of minimum battery storage is the key component to achieve the cost effective solution. An optimized control concept is studied and the result show excellent outcome. For high-end potential energy consumers, who required reliable power supply, can also be accommodated using this optimized control concept. This released the stress on electricity suppliers as well as the consumers. The proposed optimized control open up new business strategy while categorizing confirmed reliable supply feeders. This will be the first step towards introducing reliable supply similar to the developed countries.
Keywords: State of energy; Optimized control; Reliable supply; Optimized operation of islanded solar PV system.